Wastewater irrigation in Maharashtra: an exploration - Palrecha, A.; Sakhare, N.; Patkar, S.; Sule, S.; Sebastian, S.; Ramola, M. (International Water Management Institute, 2016)
Wastewater irrigaon is not new in Maharashtra and the Government of Maharashtra as well as farmers are beginning to recognize its value as a drought response. This Highlight presents a synthesis of eld exploraons in 11 locaons in Maharashtra which cover the extent of wastewater irrigaon; economics of wastewater and freshwater use; farmers' preferences and percepons about wastewater; and how they are adapng to its use in agriculture.